Positive resolution of the wound-healing response in lens epithelial cells by Ti3C2Tx MXene coatings for use in accommodative intraocular lens devices. (1st January 2023) - Cooksley, Grace; Dymond, Marcus K; Stewart, Nicolas A; Bucca, Giselda; Hesketh, Andrew; Lacey, Joseph; Gogotsi, Yury; Sandeman, Susan
Abstract: Cataract surgery removes the diseased lens of the eye replacing it with an intraocular lens, restoring visual acuity. However, accommodation, the lens' ability to provide dynamic change in focus, is lost. A number of accommodative intraocular lens (AIOL) designs have been considered although none have provided a truly effective clinical AIOL. Two-dimensional titanium carbide (Ti3 C2 T x ) MXene has been used as a transparent conductive electrode within an AIOL feasibility study. Nevertheless, the potential for Ti3 C2 T x to repress excessive inflammation and promote wound healing following cataract surgery has not been considered. Cataract surgery can trigger chronic inflammation and epithelial-mesenchymal transition (EMT) in residual lens epithelial cells (LECs), producing a fibrotic mass across the posterior capsule known as posterior capsule opacification (PCO). With a large surface area and capacity for surface functionalisation, MXene has properties enabling a dual purpose AIOL design with an additional therapeutic role in the repression of pathways leading to PCO development. In this study, Ti3 C2 T x MXene was investigated to determine its impact on pathways leading to chronic inflammation and EMT using an in vitro LECs model. Ti3 C2 T x MXene was synthesised and characterised using UV-vis spectroscopy, dynamic light scattering and scanning electron microscopy. Changes in markers linked to inflammation and EMT in Ti3 C2 T x -treated LECs were measured using enzyme linked immunosorbent assays, quantitative polymerase chain reaction, scratch assay, RNA sequencing for whole-cell gene expression profiling and lipidomics analysis. Ti3 C2 T x significantly reduced the expression of pro-inflammatory cytokines by interleukin 1 beta primed LECs and did not advocate EMT, promoting a positive resolution of the wound healing response. This study supports the role of Ti3 C2 T x within an AIOL design with the potential to repress key developmental pathways leading to PCO.